2013
DOI: 10.1007/s40268-013-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Adverse Effects of Short-Term Aspirin Use: A Meta-Analysis of Published Randomized Controlled Trials

Abstract: Background and ObjectivesAspirin is widely used for short-term treatment of pain, fever or colds, but there are only limited data regarding the safety of this use. To summarize the available data on this topic, we conducted a meta-analysis of the published clinical trial literature regarding the gastrointestinal adverse effects of short-term use of aspirin in comparison with placebo and other medications commonly used for the same purpose.Data Sources and MethodsAn extensive literature search identified 119,31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Secondly, whether the 30% increase in C max with the ibuprofen salt and liquid gelatine capsule formulations is associated with a decrease in gastrointestinal tolerability as suggested by Brune et al . This is difficult to assess by conventional methods as the gastrointestinal tolerability of OTC ibuprofen is similar to placebo in a range of robust clinical studies . Nevertheless, postmarketing data might identify rare side effects that are sufficiently severe for patients to report them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, whether the 30% increase in C max with the ibuprofen salt and liquid gelatine capsule formulations is associated with a decrease in gastrointestinal tolerability as suggested by Brune et al . This is difficult to assess by conventional methods as the gastrointestinal tolerability of OTC ibuprofen is similar to placebo in a range of robust clinical studies . Nevertheless, postmarketing data might identify rare side effects that are sufficiently severe for patients to report them.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of eight placebo‐controlled trials showed that gastrointestinal tolerability with OTC doses of ibuprofen (87.9%) did not differ significantly from placebo (89%) . A number of well‐designed studies confirm this apparent good gastrointestinal tolerability . However, these studies do not take account of the different formulations of NSAID ingested, which have different physicochemical properties and consequently different pharmacokinetic and pharmacodynamic profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baron et al () performed a meta‐analysis to identify adverse effects of aspirin usage, considering TM (Gupta et al, ) as an automated procedure to score articles for potential relevance to a posteriori meta‐analysis. A total of 119,310 articles were considered so TM highly eased the arduous labor required if these articles were analyzed at hand.…”
Section: Tm Applied To Medicinementioning
confidence: 99%
“…About 10 -15% of patients with life-threatening hemorrhage require invasive interventions for hemostasis, and approximately 4% of patients die from LGI bleeding (2,3). The incidence of LGI bleeding also increases with the usage of aspirin, nonsteroidal antiinflammatory drugs, and anticoagulants (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%